PENGARUH PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) II DAN KEPERCAYAAN DIRI TERHADAP KESIAPAN MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2022 UNIVERSITAS NEGERI MEDAN - Della Aulia Br Ginting; Revita Yuni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The research problem is rooted in the low level of teacher readiness and self-confidence in carrying out teaching duties among students of the 2022 Economic Education Stambuk program at Medan State University. This research is a quantitative study with an ex post facto approach. The study population consisted of all 60 students of the 2022 Economic Education Stambuk program at the Faculty of Economics, Medan State University. The sampling technique used total sampling, so the entire population was used as the research sample. introduction to the school field (PLP) II has a positive and significant effect on readiness to become a teacher with a calculated t value of 2.693 and a significance value of 0.009 < 0.05, (2) Self-confidence has a positive and significant effect on readiness to become a teacher with a calculated t value of 4.482 and a significance value of 0.001 < 0.05, (3) introduction to the school field (PLP) II and self-confidence simultaneously have a positive and significant effect on readiness to become a teacher with a calculated F value of 51.714 and a significance value of 0.001 < 0.05 and (4) the contribution of introduction to the school field (PLP) II and self-confidence to readiness to become a teacher is 63.2%, while the remaining 36.8% is influenced by other factors outside the research. Keywords: Introduction to the School Field (PLP) II, Self-Confidence, Readiness to Become a Teacher   Abstrak: Penelitian memiliki permasalahan yang dilatar belakangi rendahnya kesiapan untuk menjadi guru dan kepercayaan diri dalam melaksanakan tugas keguruan pada mahasiswa Pendidikan Ekonomi Stambuk 2022 Universitas Negeri Medan. . Penelitian ini merupakan penelitian kuantitatif dengan pendekatan ex post facto. Populasi penelitian terdiri atas seluruh mahasiswa Pendidikan Ekonomi Stambuk 2022 Fakultas Ekonomi Universitas Negeri Medan yang berjumlah 60 mahasiswa. Teknik pengambilan sampel menggunakan total sampling, sehingga seluruh populasi dijadikan sampel penelitian. pengenalan lapangan persekolahan (PLP) II berpengaruh positif dan signifikan terhadap kesiapan menjadi guru dengan nilai t hitung sebesar 2,693 dan nilai signifikansi 0,009 < 0,05, (2) Kepercayaan diri berpengaruh positif dan signifikan terhadap kesiapan menjadi guru dengan nilai t hitung sebesar 4,482 dan nilai signifikansi 0,001 < 0,05, (3) pengenalan lapangan persekolahan (PLP) II dan kepercayaan diri secara simultan berpengaruh positif dan signifikan terhadap kesiapan menjadi guru dengan nilai F hitung sebesar 51,714 dan nilai signifikansi 0,001 < 0,05 dan (4) kontribusi pengenalan lapangan persekolahan (PLP) II dan kepercayaan diri terhadap kesiapan menjadi guru sebesar 63,2%, sedangkan sisanya sebesar 36,8% dipengaruhi oleh faktor lain di luar penelitian. Kata Kunci: Pengenalan Lapangan Persekolahan (PLP) II, Kepercayaan Diri Kesiapan Menjadi Guru